Vocalisation and Call Activity Pattern of Sunda Scops Owl (Otus lempiji) (Aves: Strigidae) in Kubah National Park, Sarawak - Wee, Jasmine Sui Ling (Universiti Malaysia Sarawak (UNIMAS), 2017)
Sunda Scops Owl (Otus lempiji) is a common owl that is widely distributed in Southeast Asia mainly in Malay Peninsular, Bali, Sumatra and Borneo. In this study, the vocalisation and call activity pattern ofthe Sunda Scops Owl was described. This study was conducted at the Frog Pond in Kubah National Park (KNP), Sarawak from July to September 2015. The owl calls were recorded using a passive automatic recording system (i.e. Song Meter 3). There are two objectives ofthis study which are to document the vocalisation ofSunda Scops Owl Sarawak and to determine the call activity pattern of Sunda scops owl in KNP. The vocalisation ofSunda Scops Owl exhibit only a single call type which is the territorial call with a musical 'woouk woouk' with an interval of 10 to 15 seconds. Spectrogram of the call notes was generated and several vocalisation parameters were analysed. The call notes frequency range from 282.03 ± 12.93 Hz to 1205.15 ± 7.28 Hz and the average note duration of Sunda scops owl is 0.67 ± 0.02 seconds. They exhibit biphasic nightly calling pattern. Peak activity was observed during the first hour after sunset (1830 1930 hr) and three hours (0330 - 0630 hr) before sunrise. The temperature and rainfall was proven as significant factors that influenced the call frequency.